2020
DOI: 10.1016/j.ijpddr.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of commercial foam Belcils® on Acanthamoeba spp

Abstract: Interest in periocular (eyelid and eyelashes margins) hygiene has attracted attention recently and a growing number of commercials eye cleanser and shampoos have been marketed. In the present study, a particular eye cleanser foam, Belcils® has been tested against trophozoites and cysts on the facultative pathogen Acanthamoeba . Viability was tested by the alamarBlue™ method and the foam was tested for the induction of programmed cell death in order to explore its mode of action. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The experiment was carried out by following the manufacturer's recommendations, and 10 5 cells/mL well were incubated for 24 h with the previously calculated IC 90 of squamins C–F ( 1 – 4 ). As previously reported ( Sifaoui et al, 2020 ), the double-staining pattern allows the identification of three groups in a cellular population: live cells will show only a low level of blue fluorescence, cells undergoing PCD will show a higher level of blue fluorescence (as chromatin condenses), and dead cells will show low-blue and high-red fluorescence (as the Propidium Iodide stain (Life Technologies, Madrid, Spain) enters the nucleus).…”
Section: Methodsmentioning
confidence: 66%
“…The experiment was carried out by following the manufacturer's recommendations, and 10 5 cells/mL well were incubated for 24 h with the previously calculated IC 90 of squamins C–F ( 1 – 4 ). As previously reported ( Sifaoui et al, 2020 ), the double-staining pattern allows the identification of three groups in a cellular population: live cells will show only a low level of blue fluorescence, cells undergoing PCD will show a higher level of blue fluorescence (as chromatin condenses), and dead cells will show low-blue and high-red fluorescence (as the Propidium Iodide stain (Life Technologies, Madrid, Spain) enters the nucleus).…”
Section: Methodsmentioning
confidence: 66%
“…Moreover, other corneal disorders such as the dry eye syndrome, is other disease derived from the use of contact lenses. Lately, diverse research studies have reported the efficacy of commercialized eye drops and ophthalmic solutions used for these other epithelial disorders, against the two life cycle stages of Acanthamoeba strains ( Sifaoui et al, 2017 , 2018 , 2020a , b ; Reyes-Batlle et al, 2019 ). Several commercialized ophthalmic solutions present preservatives such as Propylene Glycol, Benzalkonium chloride (BAK) or its derivatives such as POLYQUAD®, which have demonstrated antimicrobial ( Kinnunen et al, 1991 ; Nalawade et al, 2015 ) or anti- Acanthamoeba activity ( Sunada et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%